Decades of quaternary research in Eastern Africa: Implications for sustainable future - Lejju, Julius Bunny; Morgan, Andama (My University, 2020)
The 5th East African Quaternary Research Association (EAQUA) workshop was themed “Decades of Quaternary Research in Eastern Africa: Implications for Sustainable Future”. It was intended to foster ways of integrating the long-term scientific information of vari¬ous paleo studies in eastern Africa from the last six decades to address future environ¬mental challenges in the region. In addition, the workshop was meant to integrate the rich paleo information into practical applications to address the social and environmental challenges affecting the region.
Keywords: Quaternary research; Workshop; Environmental challenges